Optimizing young tennis players` development: Exploring the impact of emerging technologies on training effectiveness and technical skills acquisition - Liu, S.; Wu, C.; Xiao, S.; Liu, Y.; Song, Y. (PLOS ONE, 2024)
The research analyzed the effect of weekly training plans, physical training frequency, AI-powered coaching systems, virtual reality (VR) training environments, wearable sensors on developing technical tennis skills, with and personalized learning as a mediator. It adopted a quantitative survey method, using primary data from 374 young tennis players. The model fitness was evaluated using confirmatory factor analysis (CFA), while the hypotheses were evaluated using structural equation modeling (SEM). The model fitness was confirmed through CFA, demonstrating high fit indices: CFI = 0.924, TLI = 0.913, IFI = 0.924, RMSEA = 0.057, and SRMR = 0.041, indicating a robust model fit. Hypotheses testing revealed that physical training frequency (ß = 0.198, p = 0.000), AI-powered coaching systems (ß = 0.349, p = 0.000), virtual reality training environments (ß = 0.476, p = 0.000), and wearable sensors (ß = 0.171, p = 0.000) significantly influenced technical skills acquisition. In contrast, the weekly training plan (ß = 0.024, p = 0.834) and personalized learning (ß = -0.045, p = 0.81) did not have a significant effect. Mediation analysis revealed that personalized learning was not a significant mediator between training methods/technologies and acquiring technical abilities. The results revealed that physical training frequency, AI-powered coaching systems, virtual reality training environments, and wearable sensors significantly influenced technical skills acquisition. However, personalized learning did not have a significant mediation effect. The study recommended that young tennis players` organizations and stakeholders consider investing in emerging technologies and training methods. Effective training should be given to coaches on effectively integrating emerging technologies into coaching regimens and practices.